2018
DOI: 10.1016/j.joen.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Root Canal Morphology Evaluation of Central and Lateral Mandibular Incisors Using Cone-beam Computed Tomography in an Israeli Population

Abstract: The occurrence of more than 1 root canal in central and lateral mandibular incisors is approximately 40% (type III was the predominant canal type). In central and lateral incisors with 1 root canal, long oval canals are common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 32 publications
(44 reference statements)
7
53
1
6
Order By: Relevance
“…The same finding was observed for mandibular canines in the present study. These results are once more supported by previous studies in which the occurrence of a Vertucci type I root canal in mandibular canines is recurrently higher in Chinese studies (97.0% [24], 95.8% [23], and 93.7% [30]) compared with predominantly white countries (78.0% in Brazil [21]) or any other region (66.8% in Georgia [28], 71.8% in Iran [26], 79.6% in India [31], and 89.7% in Israel [32]).…”
Section: Clinical Researchmentioning
confidence: 99%
“…The same finding was observed for mandibular canines in the present study. These results are once more supported by previous studies in which the occurrence of a Vertucci type I root canal in mandibular canines is recurrently higher in Chinese studies (97.0% [24], 95.8% [23], and 93.7% [30]) compared with predominantly white countries (78.0% in Brazil [21]) or any other region (66.8% in Georgia [28], 71.8% in Iran [26], 79.6% in India [31], and 89.7% in Israel [32]).…”
Section: Clinical Researchmentioning
confidence: 99%
“…A review of the literature revealed that using CBCT to assess symmetry in roots and/or root canal morphology in the mandibular anterior teeth has been performed only in Chinese, Turkish, Chongqing, and Israeli populations [2,12,27,36]. There is little data in the literature concerning procedures in which 2 opposite teeth are treated in the same patient, even though this topic is highly clinically relevant [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…Pécora et al 18 studied the internal anatomy, the direction, and number of roots in mandibular canines on 830 mandibular canines, and found that only 1.2% had two canals with two orifices in a single root, and 1.7% of the examined teeth had two separate roots. Shemesh et al 19 in their study found that up to 20% of mandibular canines have root canal separation and up to 6.8% are bifurcated teeth. Moreover, a…”
Section: Discussionmentioning
confidence: 96%